2020
DOI: 10.1002/jmv.26389
|View full text |Cite
|
Sign up to set email alerts
|

The effect of smoking on COVID‐19 severity: A systematic review and meta‐analysis

Abstract: Various comorbidities represent risk factors for severe coronavirus disease 2019 (COVID‐19). The impact of smoking on COVID‐19 severity has been previously reported in several meta‐analyses limited by small sample sizes and poor methodology. We aimed to rigorously and definitively quantify the effects of smoking on COVID‐19 severity. MEDLINE, Embase, CENTRAL, and Web of Science were searched between 1 December 2019 and 2 June 2020. Studies reporting smoking status of hospitalized patients with different severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
280
5
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 348 publications
(341 citation statements)
references
References 100 publications
24
280
5
7
Order By: Relevance
“…Together with DM, all these risk factors contribute to the exacerbation of preexisting chronic inflammation, progressing to cytokine storm and rapid impairment of endothelial function, if left untreated [28]. The low prevalence of smoking in the study (2.6%) is in alignment with several retrospective observational studies that highlight the unexpectedly low prevalence of smokers among hospitalized patients with Covid-19, but with worse outcomes [29,30]. Other significant factors for poor outcomes identified in the present study are the use of β-blockers and severe vitamin D deficiency among admitted Covid-19 patients.…”
Section: Established Predictors and Potential Factors Influencing Covsupporting
confidence: 60%
“…Together with DM, all these risk factors contribute to the exacerbation of preexisting chronic inflammation, progressing to cytokine storm and rapid impairment of endothelial function, if left untreated [28]. The low prevalence of smoking in the study (2.6%) is in alignment with several retrospective observational studies that highlight the unexpectedly low prevalence of smokers among hospitalized patients with Covid-19, but with worse outcomes [29,30]. Other significant factors for poor outcomes identified in the present study are the use of β-blockers and severe vitamin D deficiency among admitted Covid-19 patients.…”
Section: Established Predictors and Potential Factors Influencing Covsupporting
confidence: 60%
“…However, as the authors rightly state, this multivariable-adjusted HR cannot capture any causal effect of smoking due to adjustments for conditions that may mediate a smoking effect. (2) Quality, not just quantity Commendably, the meta-analysis in question did perform a valuable sensitivity analysis showing that when only analyzing goodquality studies, the effects of smoking became nonsignificant 3. Ignoring the debate around the "value of the p-value," 8 this demonstrates the importance of sensitivity analysis, rigorous appraisal of study quality, underlines the concept of "research waste,"1 and probably really suggests that the best available evidence in hospitalized patients shows a noncommittal result.…”
mentioning
confidence: 99%
“…Among hospitalized patients, the risk of developing severe COVID-19 (as measured by admission to the intensive care unit and/or in-hospital death) is consistently higher among smokers. The largest meta-analysis to date included 47 studies with a total of 32,849 hospitalized COVID-19 patients (Reddy et al 2020) and confirmed that current smokers had an increased risk of severe COVID-19 (risk ratio [RR]: 1.80; 95% confidence interval [CI]: 1.14-2.85; p = 0.012) and severe or critical COVID-19 (RR: 1.98; CI: 1.16-3.38; p = 0.012). A history of smoking was associated with severe COVID-19 (RR: 1.31; CI: 1.12-1.54; p = 0.001), severe or critical COVID-19 (RR: 1.35; CI: 1.19-1.53; p < 0.0001), in-hospital mortality (RR: 1.26; CI: 1.20-1.32; p < 0.0001), progression of COVID-19 (RR: 2.18; CI: 1.06-4.49; p = 0.035), and need for mechanical ventilation (RR: 1.20; CI: 1.01-1.42; p = 0.043).…”
Section: Smoking Is a Prognostic Factor For Covid-19mentioning
confidence: 99%